A produção cinematográfica independente no cenário carioca de 2019 a 2022 - Gonçalves, Eduardo Boone (2023)
The research discusses the independent film production model in the city of Rio de Janeiro from 2019 to 2022, aiming to analyze the concept of independent production and relate the model proposed by the authors to the one executed by producers in Rio de Janeiro. The central argument acknowledges the functioning of this production model arising from partnerships between professionals and friends. Independent production is understood as that which is done without funding from public grants, being a cinema of scarce resources and creativity. In a bibliographic research, a semi-structured script was developed with questions aimed at Rio de Janeiro producers. The production model changes with the advent of technologies, and independent production makes the act of filmmaking more accessible to everyone